The Dances of Doris Humphrey - Creating a Contemporary Perspective through Directorial Interpretation - Main, Lesley (Edinburgh: Edinburgh University Press, 2005)
RESUMEN: It has been widely acknowledged that Doris Humphrey and Martha graham were the two most influential exponents of American modern dance. Graham's work has been the more prominent, in part because she outlived Humphrey by thirty-two years and performed for a much longer period. This does not, however, diminish the influence that Humphrey's work has had on modern dance since her death in 1958. More significant, perhaps, is the influence it can have in the future. Humphrey's legacy includes a certain amount of documentary literature, including her seminal book on the craft of choreography, the Art of Making Dances (1959). This article will discuss strategies undertaken to develop a perspective on modern dance production, including the significance of style; the search for a "living past" drawing on the ideas of R. G. Collingwood; the identification, viewing and interpretation of evidence, including the use of a Labanotation score. The production processes employed by a range of artists involved in reconstruction will be considered, and my own practice positioned in relation to this. The notion of co-authorship will be examined within the contexts of these respective practices, illustrated by examples from recent Humphrey productions.